PENGARUH CURRENT RATIO, DEBT TO EQUITY RATIO DAN RETURN ON ASSET TERHADAP HARGA SAHAM PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Silvani Okta Faradina, 10.05.52.0024; Sri Mindarti, Ceacilia (Students Journal of Accounting and Banking, 2014)
Capital market existence in Indonesia is marked with to the number of investor that start inculcate its share in industry manufacturing. Growing fast its sector growth this manufactur is followed with growing request height of board need, until make investors manufactur requires fund from external source. Fund was from external source can be obtained pass bycapital market. The objectives of this research to analyze current ratio, debt to equity ratio, and return on assetto stock price of manufacturing industryt hat listed on Indonesian Stock Exchange in the period of 2010-2012. The data is obtained based on Indonesian Capital Market Directory (2010, 2011 and 2012)Â publication. Sample of this research amount of 71 companiesÂ from 146 manufactur companies those are listed in BEI. Multiple regression and hypothesis test using t-statistic is used to examine partial regression coefficient and f-statistic to examine the mean of mutual effect with level of significance 5%. InÂ addition,Â classical assumptionÂ test also performed including normality test, multicolinearity test, heteroscedasticity test and autocorrelation test. The multiple regression shows that Current Ratio hasnât significant negative effect on stock prices, while Debt to Equity Ratio hasnât significant positive effect on stock price and Return on Asset significant positive effect on stock price. Keywords: Stock Price, Current Ratio, Debt to Equity Ratio and Return on Asset